If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.5(-12m + 6) = 0.25(-20 + 8m) Reorder the terms: 0.5(6 + -12m) = 0.25(-20 + 8m) (6 * 0.5 + -12m * 0.5) = 0.25(-20 + 8m) (3 + -6m) = 0.25(-20 + 8m) 3 + -6m = (-20 * 0.25 + 8m * 0.25) 3 + -6m = (-5 + 2m) Solving 3 + -6m = -5 + 2m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-2m' to each side of the equation. 3 + -6m + -2m = -5 + 2m + -2m Combine like terms: -6m + -2m = -8m 3 + -8m = -5 + 2m + -2m Combine like terms: 2m + -2m = 0 3 + -8m = -5 + 0 3 + -8m = -5 Add '-3' to each side of the equation. 3 + -3 + -8m = -5 + -3 Combine like terms: 3 + -3 = 0 0 + -8m = -5 + -3 -8m = -5 + -3 Combine like terms: -5 + -3 = -8 -8m = -8 Divide each side by '-8'. m = 1 Simplifying m = 1
| (-8x-7)(-7x-3)= | | N+19=16 | | 6x^2+78x=-216 | | (8x+6)(8x^2+7x+8)= | | 8c*3e= | | -p-2p+3=-6 | | 6+x+-5+2x=x | | 29=2u+13 | | X-3=7-4x | | 6m^2+11m+4=0 | | 5(-2x-4)-3(4+5)=97 | | 0.58+x=133.98 | | 4+y=13-4(y+1) | | x+-17=y | | 6x^4-8x^2+3/8x^2 | | 7-8(k+3)=-10-9k | | 3(x+1)-10=-4(2x-3)+14 | | 4acx*5ax^2*6c= | | x+0.58=133.98 | | 6+-5+2x=x | | 9d+-2d+4=32 | | 9mn*2m^2n= | | (8*x)-7=y | | 4(y-9)=-6(7+y) | | 6a*3a= | | .7w-0.4+0.2w=5 | | 6(10+4x)=156 | | 3x+5=12x-10 | | 3x-9=3x-6 | | 0.7w-0.4+0.2w=5 | | 11x/20-8=x/5+27 | | 8a^2c^5(-2a^3/c^2) |